2018
DOI: 10.1071/rd18063
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of cauda epididymal plasma improves sperm characteristics following liquid preservation of ram semen at 3–5°C

Abstract: Mammalian spermatozoa remain immotile and metabolically inactive in the cauda epididymidis, thus maintaining fertility for several weeks. The aim of this study was to functionally characterise and evaluate the effect of cauda epididymal plasma (CEP) on liquid preservation of ram spermatozoa. Four experiments were conducted to investigate the effects of: (1) CEP and its fractions on sperm motility; (2) CEP (10%, 15%, 20% v/v) on liquid preservation of ram spermatozoa; (3) seminal plasma (SP; 20%, 30%, 50% v/v) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…Considerable progress in semen preservation has been made over the past few decades; however, the decline that occurs in sperm quality during this process has not been resolved [5,11,20]. During in vitro preservation, there is a risk of oxidative damage to sperm owing to ROS accumulation [8,12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Considerable progress in semen preservation has been made over the past few decades; however, the decline that occurs in sperm quality during this process has not been resolved [5,11,20]. During in vitro preservation, there is a risk of oxidative damage to sperm owing to ROS accumulation [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS damages cellular proteins, and the lipid structure of the cell membrane, furthermore excessive ROS causes gene mutations and accelerates cell death [10]. Previous studies have shown that the addition of antioxidants can significantly improve sperm quality in the rat [22], bull [11], dog [12], boar [8], and ram [5] by reducing ROS accumulation during the preservation process. GSPE has been reported to have a strong antioxidant capacity [13,15,16,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations